CO-RABS Score: A Novel Bedside Scale to Predict the Severity in COVID Patients - Merugolu Finny Theo Joseph; Dabboo Patwari; Kishore Kumar Talukdar; Bhaskar Neog; Sunny Kumar Yadav; Nasimur Riaz (Assam Journal of Internal Medicine)
Study Objective: To determine the prognostic significance of a new score (CO-RABS), formulated by our Institute to classify the covid patients into mild, moderate, severe cases and also to compare it with the conversion AIIMS based classification. Patients and Methods: This is a retrospective study in which we have collected data from the medical records of patients who were admitted in our Hospital with covid infection during 2nd and 3rd waves of the pandemic. We have taken Comorbidities (CO), Respiratory rate (R), Age (A), Blood pressure (B) and SpO2 (S) of the patients at the time of admission to calculate an overall score (Abbreviated as CO-RABS). Basing on this score, the patients were classified into mild, moderate and severe cases. We then compared our CO-RABS score based classification with AIIMS classification using a statistical software. Results: We studied 727 patients (440 men, 287 women) and 99 patients died due to covid related complications. The ability to predict the prognosis was higher for our newly formulated CO-RABS score when compared to AIIMS classification. (AUC of CO-RABS 0.88 vs 0.82 of AIIMS; p < 0.05). Conclusion: The ability of CO-RABS score to predict the prognosis of covid infection is higher than that of AIIMS/ICMR classification. Hence it can be used as a supportive tool in the covid management protocol along with all the other conversion modes of treatment.